An investigation of the relationship between colour preference and the purchase intention within the luxury garment industry in South Africa - Moloi, Modula (The IIE, 2022)
A consumer's decision can be characterised as their personal approach to making a choice. The choice they make when considering to purchase a product is based on the visual elements of that said product. Colour plays an important role in visual merchandising as it influences consumer behaviour and their purchase decision. The fashion industry has a large contribution to the creative industries, its value to urban development and promotion has become increasingly recognised. The industry has grown to include Africa and Asia, where countries such as South Africa are no longer subjected to fashion trends but are now aiming to global industry leaders. The study aims to determine whether a correlation in the purchasing intent of women buying luxury garments based on colour trends exist. This study will make use of correlational research. The sample size of 40 will be considered for participate in the study. The researcher will explore existing literature that test theories similar to the study being conducted and then they will apply the theories to the more specific topic of the investigation. They will link the information generated from the initial research to the research proposal keeping in mind a specific conclusion Through the use of descriptive states, the researcher will be able to assess the data according to the measures of frequency, central tendency and dispersion. The findings highlighted the importance of colour in purchasing garments. It will also give the researcher an understanding of the meaning of colour to the different consumers according to their age. The study may be able to provide future researchers with a foundation to further investigate if colour and colour palettes can be used to segment markets.
Keywords: Color; Fashion; Customer behaviour; Buying patterns